Possíveis benefícios do óleo essencial de Alpinia zerumbet sobre os sintomas negativos e cognitivos da esquizofrenia induzidos pela administração de cetamina em ratos - Galdino, Daniel Sobreira (2013)
Antipsychotics represent the basis in treatment of schizophrenia, a severe mental disorder, disabling, with high social burden. Schizophrenia is a syndrome characterized by the presence of positive, negative and cognitive symptoms. The current therapy does not manage satisfactorily the negative and cognitive symptoms. One of the most relevant models for the study of schizophrenia in a preclinical approach is the administration of ketamine. In this sense the repeated administration of the drug can largely mimic the symptoms of schizophrenia in rodents. The Alpinia zerumbet is a plant whose essential oil (EOAZ) has shown significant antipsychotic effect as evidenced in previous studies of our research group. Based on this statement the present study aimed to determine the effects of EOAZ against positive, negative and cognitive schizophrenia induced by acute and repeated administration of ketamine-like symptoms. For this it was used male Wistar rats treated with EOAZ 100 or 200 mg/kg alone or following the administration of ketamine. In repeated administration protocol ketamine was applied for five days and in the subsequent five days the animals received both ketamine and EOAZ 100 or 200 mg/kg. One group of animals was treated with the atypical antipsychotic risperidone and other received saline (control). After treatment the animals were subjected to behavioral assessments for the determination of positive symptoms (locomotor activity) , negative (social interaction) and cognitive (Y maze and object recognition memory) . The results showed that acute administration of ketamine was not able to cause changes in all models used , especially in relation to recognition memory of objects that was even enhanced by acute drug administration. The EOAZ at both doses was able to reverse those changes. Repeated administration of ketamine was able to mimic more accurately the changes related to schizophrenia , and in this model the administration of EOAZ was superior to risperidone , particularly in working memory. Therefore, the results of this study show that EOAZ may be a new pharmacological approach in treating negative and cognitive symptoms of schizophrenia.